Generalized F-contraction Mapping in G-Metric Spaces and Some Fixed Point Results - Bhatia, Vinod; Harsh Kumar (International Journal of Computational and Experimental Science and Engineering, 2025)
In this research paper, we define some new notions of generalized F-contraction of type (L) and type (J) in G-metric spaces. By using these notions we define some fixed point theorems. We also provided an example to justify our results.